Immunological methods in microbiology - Gurtler, Volker; Pavia, Charles S. (Methods in microbiology ;, 2020)
"Immunological Methods in Microbiology, Volume 47 in the Methods in Microbiology series, highlights new advances in the field, with this new volume presenting interesting chapters on Immunological Techniques in the Clinical laboratory, Immunologic Diagnosis of HIV and Opportunistic Infections, Combining Antigen Detection and Serology for the Diagnosis of Selected Infectious Diseases, Immunologic Detection of Lyme Disease and Related Borrelioses, Immunodetection of Bacteria Causing Brucellosis, Immunological Diagnostic Techniques Used to Identify and Type Pasteurella, Immunological Tests for Diarrhea caused by Diarrheagenic Escherichia coli Targeting Their Main Virulence Factors, and much more."--Publisher's web page (viewed April 29, 2020)